Effect of the plasma-induced magnetic field on a magnetic nozzle. (21st June 2016) - Merino, Mario; Ahedo, Eduardo
Abstract: A two-fluid, two-dimensional model of the plasma expansion in a divergent magnetic nozzle is used to investigate the effect of the plasma-induced magnetic field on the acceleration and divergence of the plasma jet self-consistently. The induced field is diamagnetic and opposes the applied one, increasing the divergence of the magnetic nozzle and weakening its strength. This has a direct impact on the propulsive performance of the device, the demagnetization and detachment of the plasma, and can lead to the appearance of zero-field points and separatrix surfaces downstream. In contrast, the azimuthal induced field, albeit non-zero, is small in all cases of practical interest.